Phylogeography of the Asian green mussel, Perna viridis: pronounced regional genetic differentiation is explained by major freshwater input into the Bay of Bengal - Gardner, Jonathan P. A.; Patterson, Jamila; Patterson, Edward J. K. (Frontiers in Marine Science, 2023)
The Asian green mussel (AGM), Perna viridis, is a mussel of ecological and economic importance throughout much of the tropical and subtropical regions of Asia, from China and Korea in the east to Oman on the Arabian Peninsula in the west. We collated published DNA sequence data and then analysed 467 bp of cytochrome c oxidase I gene (COI) sequence variation from 649 mussels (576 from SE Asia and 73 from India) to test for regional differentiation. Analysis of molecular variation, a haplotype network and a neighbour-joining tree all revealed significant differentiation between mussels from India and those from SE Asia. We observed a greater number of segregating sites (haplotypes) and private haplotypes than expected for Indian mussels compared to SE Asian mussels, based on the respective sample sizes. Tests of neutrality revealed population expansion or a recent selective sweep for only the mussels from India. We suggest that the differentiation of the Indian from the SE Asian mussels is explained by the pronounced seasonal input of freshwater into the northern Bay of Bengal area, which acts as a putative (semi-permeable) barrier to gene flow between the two regions (i.e., east versus west of the Bay). This suggestion is based on the oceanography of the region and is consistent with the biogeography and reports of genetic breaks in a range of taxa in this region. Further targetted sampling of AGMs from the east coast of India, Bangladesh and Myanmar is required to test this hypothesis, and additional sampling of AGMs from west of India (e.g., Pakistan, Iran, the Arabian Peninsula) will also be informative. Finally, this study is based on the analysis of a single marker (COI) because this is all that is presently available from published sources but we note that the application of new molecular markers such as single nucleotide polymorphisms to newly collected mussel samples will greatly advance our understanding of the AGM genetic discontinuity and its timing, and help test its geographical location (extent) and its nature (e.g., a steep/shallow cline or a stepped cline).